Lymphoproliferation Impairment and Oxidative Stress in Blood Cells from Early Parkinson’s Disease Patients - Vida, Carmen; Kobayashi, Hikaru; Garrido, Antonio; Martínez de Toda, Irene; Carro, Eva; Molina, José Antonio; De la Fuente, Mónica (International journal of molecular sciences, 2019)
In Parkinson’s Disease (PD), the peripheral changes in the functional capacity and redox state of immune cells has been scarcely investigated, especially in the early PD stages. Aging is a risk factor for PD, and the age-related impairment of the immune system, based on a chronic-oxidative stress situation, is involved in the rate of aging. We analyzed several functions in isolated peripheral blood neutrophils and mononuclear cells from PD stage 2 patients, and compared the results to those in healthy elderly and adult controls. Several oxidative stress and damage parameters were studied in whole blood cells. The results showed an impairment of the lymphoproliferative response in stimulated conditions in the PD patients compared with age-matched controls, who also showed typical immunosenescence in comparison with adult individuals. Higher oxidative stress and damage were observed in whole blood cells from PD patients (lower glutathione peroxidase activity, and higher oxidized glutathione and malondialdehyde contents). Our results suggest an accelerated immunosenescence in PD stage 2, and that several of the parameters studied could be appropriate peripheral biomarkers in the early stages of PD.